Copolymer Micelles: A Focus on Recent Advances for Stimulus-Responsive Delivery of Proteins and Peptides - Thomas Trimaille; Bernard Verrier (MDPI AG, 2023)
Historically used for the delivery of hydrophobic drugs through core encapsulation, amphiphilic copolymer micelles have also more recently appeared as potent nano-systems to deliver protein and peptide therapeutics. In addition to ease and reproducibility of preparation, micelles are chemically versatile as hydrophobic/hydrophilic segments can be tuned to afford protein immobilization through different approaches, including non-covalent interactions (e.g., electrostatic, hydrophobic) and covalent conjugation, while generally maintaining protein biological activity. Similar to many other drugs, protein/peptide delivery is increasingly focused on stimuli-responsive nano-systems able to afford triggered and controlled release in time and space, thereby improving therapeutic efficacy and limiting side effects. This short review discusses advances in the design of such micelles over the past decade, with an emphasis on stimuli-responsive properties for optimized protein/peptide delivery.